Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Pada PT. Aplikanusa Lintasarta Medan - Widyatul Hidayah; Arnida Wahyuni Lubis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the current era of globalization, many companies provide services, especially in the field of information and communication technology, one of which is PT. Applications Lintasarta. This company is a subsidiary of Indosat Ooredo Hutchison (IOH) which operates in the field of providing data communications networks, internet and IT services. This research aims to analyze the factors that influence employee performance at PT. Aplikanusa Lintasarta Medan. This research is a qualitative descriptive research, the subjects of this research are employees of PT. Aplikanusa Lintasarta Medan. Data collection was carried out using observation and interview techniques. The results of this research are that compensation, career path and employee image are influenced by employee performance. In procurement, performance indicators are close to the theory, namely quality, quantity, time, cost reduction and supervision. As well as bias conditions, the halo effect and the influence of the last impression still occur when evaluating employee performance. Suggestions that can be used to improve the quality of employee performance at PT Aplikanusa Lintasarta Medan are to create assessment indicators using numbers so that bias conditions, halo effects and the influence of last impressions do not occur in the assessment.